IMMU-46. LINEAGE DEPLETED HEMATOPOIETIC STEM CELLS POTENTIATE IMMUNE CHECKPOINT RESPONSE TO ANTI-PD1 AND ANTI-CD276 IN MURINE GLIOMA. (9th November 2020) - Larkin, Trisha; Cruz, Marjorie; Flores, Catherine
Abstract: INTRODUCTION: Glioblastoma multiforme (GBM) is a malignant brain tumor with rapid growth and infiltration, high treatment resistance, and dismal survival. Intratumoral heterogeneity and poor CNS penetration contribute to treatment resistance. Flores et al. demonstrated that hematopoietic stem cell transfer could reprogram gene expression within the tumor microenvironment, sensitizing glioma-bearing mice to treatment with immune checkpoint blockade. The objectives of this study are to expand on the role of HSCs in potentiating efficacy to immune checkpoint blockade with anti-PD1 and anti-CD276. METHODS: KR158B murine glioma cells were implanted into the caudate nucleus of C57BL/6 mice. Hematopoietic stem cells were derived from naïve syngeneic mice and lineage depleted using the CliniMacs system. On Day 5, HSCs (10 5 cells) were administered. Anti-CD276 and PD-1 monoclonal antibodies were administered every five days for a total of four dose administrations. Mice to allocated to no treatment, anti-CD276 only, or HSCs with or without PD1 and anti-CD276. Groups were followed for survival. Data was analyzed with GraphPad Prism. RESULTS: The combination of lineage depleted HSCs + anti-CD276led to increased median survival when compared to the survival of mice treated with anti-CD276 monotherapy with the mice who received the combination surviving for a median of 62 days versus 36 days (p = 0.001, CI 0.204 to 1.655). The combination of HSCs + PD-1 therapy led to increased median survival of 60 days and long-term survivors, replicating prior findings from our group. Mice treated with HSC transfer, anti-B7-H3, and anti-PD-1 demonstrated a median survival of 76 days (p = 0.037). CONCLUSION: We demonstrate a compounded survival effect when anti-B7-H3 and anti-PD1 were administered together with lineage depleted HSCs, suggesting an expanded avenue for overcoming treatment resistance. Future studies will be important to characterize the immune effects of combinatorial immune checkpoint administration with adjuvant HSC transfer.